Research on the Architecture and Control Technology of Virtual Coupling System for Autonomous-rail Rapid Trams - YUAN Xiwen; HE Chuan; HUANG Qiang; ZHANG Xinrui; HUANG Ruipeng; XIAO Lei (Kongzhi Yu Xinxi Jishu)
Scenarios such as tidal passenger flow, instantaneous large passenger flow, and mixed operation demand an increasing number of autonomous-rail rapid trams (ART) to increase passenger capacity. However, traditional mechanical physical coupling proves too cumbersome for convenient adjustments. This paper proposes a virtual coupling concept and system architecture for autonomous-rail rapid trams as a solution. This study developed a safe braking model and collaborative control model, in addition to establishing a collaborative planning objective function and constraints. Real-time calculations of speeds, accelerations and traction/braking force percentages for the following ART were conducted under the condition of maintaining the minimum safe distance. Simulations and experiments conducted with real trams demonstrated distances between the trams of less than 5 m, arrival time differences of less than 3 s, parking time differences between the leading and following trams of less than 0.5 s, jerks of the following tram not exceeding 0.4 m/ s3, as well as seamless switching between traction and braking during the operation of virtually coupled trams at 45 km/h. These results underscored the effectiveness of the proposed system in facilitating punctual, precise, comfortable and energy-efficient operation of virtually coupled trams. This research lays a solid foundation for potential future applications of virtually coupled ARTs at scale.